EPISTEMOLOGY OF THE ESOTERIC INTERPRETATION OF THE QUR’AN (Study about Ta’wīl al-Qur’ān) - Kerwanto, Kerwanto (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2020)
This article is anattempt to explain the episteme setting and the foundations of the diversity of theories about esoteric interpretation of the Qur’an (ta’wīl al-qurān). Such studies are important because there is still a misunderstanding of the meaning and truth of ta’wīl al-qurān. Through this article, the author wants to map discourse, look for aspects of the similarities and differences in theories about al-ta’wīl. Next, analyze the implications of the theory for the application of ta’wīl al-qurān. In addition, to exposing differences in theoretical views, this article is also intended to show the meeting point between the views of the interpreters of the Sunnah and Shi'ite, as well as between the exoteric scholars (ahl Sharīah) and esoteric scholars (ahl Ṭarīqah) about the nature of ta’wīl al-qurān. The discussion begins with a review of the definition and basic meaning of al-ta’wīl in terms of etymology and terminology. Then, the author invites the reader to examine the views of the commentators related to the requirements, classification, patterns of relation, methods and steps toward ta’wīl al-Qurān. In this article, the author shows the agreement that the exoteric meaning (ma’nā zhāhir) as the basic foundation of ta’wīl, in addition to the other differents according to how they understand the Qur’an and its nature meaning. It is explained also influence the classification and pattern of relation –chosen by commentators- on how the methods and steps work toward ta’wīl al-Qurān